Alkyl complexes of divalent lanthanides and heavy alkaline earth metals. (May 2021) - Khristolyubov, Dmitry O.; Lyubov, Dmitry M.; Trifonov, Alexander A.
Abstract : The review presents data on the synthesis, structure, reactivity, and catalytic activity of alkyl derivatives of rare earth metals in the oxidation state +2 (Sm, Eu, Yb) and their analogues containing heavy alkaline earth metals (Ca, Sr, Ba). The synthetic aspects and structural features of this unique class of organometallic compounds, which contain highly reactive M–C bonds, including alkyl, α-silylmethyl, and also benzyl, diphenylmethyl, and triphenylmethyl derivatives are considered. The bibliography includes 157 references.